Drug use disorders before, during, and after imprisonment - Mitchell, Ojmarrh (Crime and justice, 2022)
Drug-involved offenders have been long overrepresented in prisons. Intensified drug law enforcement in many countries increased both incarceration rates, especially for drug offenses, and numbers of drug-involved prisoners. This is attributable to four features of drugs and drug markets. Drug use disorders typically are not the only problems facing drug-involved prisoners. A high proportion exhibit severe mental health problems such as major depression, personality disorders, and psychotic disorders. Before incarceration, many drug-involved prisoners have unstable housing and are at high risk of homelessness; incarceration increases that risk. The high concentration of drug-involved offenders in prisons presents numerous challenges. After release, the most obvious are high rates of drug relapse and recidivism. Former prisoners have extraordinarily high risks of drug overdoses shortly after release; in the long term, diseases acquired during imprisonment are transmitted in the community. Effective prison-based drug treatment holds promise to break this cycle and mitigate physical and mental health problems of drug-involved prisoners. Unfortunately, access to treatment modalities proven to be effective in reducing drug use and recidivism is limited. A paradigm shift in drug enforcement and treatment is needed to meet the challenges presented by individuals with drug use disorders more effectively.